SOME BIOGRAPHICAL AND HISTORICAL NOTES ON JOSEPH CONRADâ€™S HEART OF DARKNESS - ., Yunhenly (Pena : Jurnal Pendidikan Bahasa dan Sastra, 2014)
Joseph Conradâ€™s novel, Heart of Darkness, based on Ratnaâ€™s classifications is the work of an author who writes his or her work[s] based on his or her direct experience (2004, p. 56). The analysis here has shown that there are many parallelisms between Marlowâ€™s narration and Conradâ€™s real experience when Conrad was in the Congo in 1890. Whilst historical perspectives also indicate that some â€œfictionalized eventsâ€ in the novel has the real references and historical contexts with the reign of King Leopold II in the Congo Free State in 1885 to 1908. Key words: parallelisms, narration, King Leopold II